126 Urinary desmosine, a biomarker of elastin degradation is significantly elevated and associated with maximum aortic root size and aortic Z-scores in patients with bicuspid aortic valve. (May 2019) - Iskandar, Zaid; Huang, Jeffrey; Miller, Lynn; Chin, Calvin; Mordi, Ify; Mcwilliam, Catherine; Goudie, David; Berg, Jonathan; Neagoie, Alex; Lang, Chim; Choy, Anna-Maria
Abstract : Introduction: Bicuspid aortic valve (BAV) affects up to 2% of the general population and is associated with a significant risk of aortic dilatation and aortic dissection. Therefore, patients are normally routinely followed up with serial echocardiography. Aortic dilatation involves elastin breakdown as part of extracellular matrix degradation. Desmosine is a specific amino acid cross-link between mature elastin molecules and is released into plasma and urine following elastin degradation. Following on from previous pilot data in the DESMA study on patients with Marfan Syndrome which demonstrated a significant correlation between plasma desmosine and aortic root size, we explored whether this same relationship is seen in patients with other forms of aortopathies, specifically the BAV cohort. Methods: Urinary and plasma desmosine were measured in 20 patients with BAV and compared to age-matched healthy controls. Urinary desmosine (uDES) and plasma desmosine (pDES) levels were measured in the same laboratory using liquid chromatography-tandem mass spectrometry (LC-MS). Results: The cohort was predominantly male (75%) and mean age was 49.3±17.3 years old. All the patients had normal LV systolic function and 9 (45%) patients had treated hypertension. Mean aortic root size was 35±5.8mm. Compared to controls, both uDES (15.9 ± 4.6 vs 7.2 ± 2.8 ng/mg creatinine, p<0.001) and pDES (0.3 ± 0.1 vs 0.26 ± 0.075 ng/mL, p=0.01) were significantly elevated in patients with BAV. Urinary desmosine was significantly correlated (Figure 1 ) with aortic root size (r=0.65, p=0.002), and aortic root z-score (r=0.59, p=0.007), however there was no significant correlation seen between plasma desmosine and aortic root size (r=0.42, p=0.06) or aortic root z-score (r=0.14, p=0.56). Conclusion: Urinary and plasma desmosine levels are significantly higher in patients with BAV compared to controls. Urinary desmosine is also significantly associated with aortic root size and z-score, reflecting higher elastin degradation in patients with larger aortic roots. This suggests a potential utility of desmosine as a biomarker in patients with BAV. Larger studies are needed to test this hypothesis. Conflict of Interest: None